Predicting shim gaps in aircraft assembly with machine learning and sparse sensing. (July 2018) - Manohar, Krithika; Hogan, Thomas; Buttrick, Jim; Banerjee, Ashis G.; Kutz, J. Nathan; Brunton, Steven L.
Highlights: Machine learning, dimensionality reduction and optimization are used to accelerate high-fidelity, measurement driven aircraft assembly. Our novel method extracts features and optimizes gap measurement locations to predict shim gaps in aircraft assembly. The proposed algorithm is demonstrated on historic Boeing aircraft production data. 99% of shim gaps are predicted within the desired measurement tolerance using 3% of the original laser scan points. Abstract: A modern aircraft may require on the order of thousands of custom shims to fill gaps between structural components in the airframe that arise due to manufacturing tolerances adding up across large structures. These shims, whether liquid or solid, are necessary to eliminate gaps, maintain structural performance, and minimize pull-down forces required to bring the aircraft into engineering nominal configuration for peak aerodynamic efficiency. Currently, gap filling is a time-consuming process, involving either expensive by-hand inspection or computations on vast quantities of measurement data from increasingly sophisticated metrology equipment. In either case, this amounts to significant delays in production, with much of the time being spent in the critical path of the aircraft assembly. In this work, we present an alternative strategy for predictive shimming, based on machine learning and sparse sensing to first learn gap distributions from historical data, and then design optimized sparse sensing strategies to streamline the collection and processing of data. This new approach is based on the assumption that patterns exist in shim distributions across aircraft, and that these patterns may be mined and used to reduce the burden of data collection and processing in future aircraft. Specifically, robust principal component analysis is used to extract low-dimensional patterns in the gap measurements while rejecting outliers. Next, optimized sparse sensors are obtained that are most informative about the dimensions of a new aircraft in these low-dimensional principal components. We demonstrate the success of the proposed approach, known within Boeing as PIXel Identification Despite Uncertainty in Sensor Technology (PIXI-DUST), on historical production data from 54 representative Boeing commercial aircraft. Our algorithm successfully predicts 99% of the shim gaps within the desired measurement tolerance using around 3% of the laser scan points that are typically required; all results are rigorously cross-validated.